Penyelesaian Permasalahan Hukum Pidana Dan Hukum Perdata Melalui Melalui Mekanisme Mediasi Oleh Mediator Desa Natar Lampung Selatan - Sonata, Depri Liber; Achmad, Deni; Farid, Muhammad; Murniarti, Rilda (FT Universitas Lampung, 2024)
The urgency of resolving criminal and civil problems through village mediators in order to increase the effectiveness and efficiency of handling problems at the village level. Village mediators have the ability to provide solutions that are fast and more accommodating to village values compared to formal judicial processes. This mediation approach encourages the resolution of legal conflicts peacefully and through deliberation, which can strengthen social relations and prevent conflict escalation. In addition, village mediators have a deep understanding of the local social and cultural context, so that the mediation process becomes more relevant and accepted by the community. This activity aims to increase awareness and knowledge regarding the resolution of criminal and civil problems through village mediators in Natar Village. The methods used to achieve these objectives are the delivery of materials through counseling, focused discussions, and questions and answers. This activity is located in Natar Village.